Wh-Questions In English, Najdi Arabic, Upper Egyptian Arabic: A Comparative Study - Alajmi, Mashael Hamed; Alsager, Haroon N. (Ijaz Arabi Journal of Arabic Learning, 2023)
This paper investigates the wh-questions strategies in Najdi Arabic (NA), Upper Egyptian Arabic (UEA), and English (E) and aims to make a comparison between them. The method in this paper is qualitative; its data are derived from previous studies in the field of the syntax of wh-question of Arabic dialects, both argument and adjuncts. Both NA and UEA use the gap, class 2 gap strategy, resumptive and class 2 resumptive strategy, and in situ strategy. The result shows that Arabic dialects are more productive than English in question structures in both argument and adjuncts wh-questions. English does not use resumptive and resumptive class 2 strategies because no pronominal addition is attached to the main verb in the English questions structure.